Clinton, new terrorism and the origins of the war on terror - Tsui, Chin-Kuei (Routledge studies in US foreign policy, 2017)
The origins of the War on Terror and the myth of President George W. Bush's foreign policy revolution -- Framing the threat of new terrorism: the invention of U.S. terrorism discourse, and President Clinton's counterterrorism approach -- Conceptualisating terrorist attacks: metaphors, frames, and President Clinton's counterterrorism initiatives -- Framing the threat of rogue states: Iraq, Iran, and Clinton's dual-containment approach to Middle East peace -- Writing American national identity: narratives and the social construction of terrorism as a negative ideograph -- Rethinking the discursive construction of terrorism and counterterrorism: theoretical reflections and implications